PENGARUH DANA PERIMBANGAN DAN PENDAPATAN ASLI DAERAH (PAD) TERHADAP BELANJA DAERAH KOTA TUAL PERIODE 2010-2013 - Ely Steven Ingratubun; Wilhaminus Sombolayuk (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2019)
This study aims to determine and analyze how much influence simultaneously from the balance funds and local original income to the regional expenditure of Tual city while partially to find out and analyze how much influence the regional balance funds and original revenue (PAD) to the Tual city regional expenditure. The results showed that if the variable X1 (balancing fund) and X2 variable (local original income), affect the regional expenditure in Tual City. So the variables X1 (balancing funds) and X2 (local own revenue) simultaneously (together) affect the Tual City government regional expenditure. To maintain the consistency of the Tual city government budget, it is necessary to do: (1) The Tual city government focus on increasing balance funds in order to spur the regional economy more effectively and efficiently in the future, (2) Tual City government, more focus on building infrastructure such as bridges / ports, terminals, shophouses, fish markets, vegetable markets, clothing markets, fruit markets and others in order to increase regional own-source revenue (PAD) going forward, and (3) Tual city government further strengthens bureaucratic performance in increasing funds regional balance and original revenue in order to increase the regional budget more effectively and efficiently in the future.